2017
DOI: 10.1080/13607863.2017.1348466
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with daily challenges in dementia (deal-id study): process evaluation of the experience sampling method intervention ‘Partner in Sight’ for spousal caregivers of people with dementia

Abstract: Although recruitment barriers were encountered, results indicate that future implementation of the ESM intervention 'Partner in Sight' is likely to be feasible in regular health care. If the intervention turns out to be (cost-) effective, a fine-tuned version of the program could be a valuable addition to the current health care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…Of the 18 participants, 13 individuals experienced this as pleasant or neutral, but 4 reported this to be unpleasant. Similar side-effects of the ESM have previously been reported, and a suggestion could be to use positive formulations in the ESM questions [ 44 ]. For example, instead of asking about cognitive problems (eg, “Since the last beep, I had memory problems”), abilities could be targeted instead (eg, “I can remember well”).…”
Section: Discussionsupporting
confidence: 74%
“…Of the 18 participants, 13 individuals experienced this as pleasant or neutral, but 4 reported this to be unpleasant. Similar side-effects of the ESM have previously been reported, and a suggestion could be to use positive formulations in the ESM questions [ 44 ]. For example, instead of asking about cognitive problems (eg, “Since the last beep, I had memory problems”), abilities could be targeted instead (eg, “I can remember well”).…”
Section: Discussionsupporting
confidence: 74%
“…These findings indicate suboptimal implementation of the advice of movement disorder experts communicated in a letter, as typically done in standard outpatient settings, and that other medical consultation models may be more appropriate for this population. This is in line with previous studies, with more elaborate interventions, that reported low adherence in interventions aiming at improving quality of disease management in elderly populations [47][48][49][50][51]. Perhaps the most important result of this trial is that we identified several barriers for the implementation of the advice.…”
Section: Discussionsupporting
confidence: 89%
“…The process evaluation in intersec-CM is focusing on the intervention itself. Based on further process evaluation designs [10][11][12][13][14][15][16], we defined dimensions and research questions focusing on relevant key actors of the ICM in routine care.…”
Section: Methodsmentioning
confidence: 99%
“…The deal-id study investigated how feedback for caregivers/relatives of persons with dementia elicits positive emotions. The corresponding process evaluation analysed sampling quality (recruitment and randomisation, reach) and intervention quality (relevance and feasibility, adherence to protocol) [ 13 ]. A process evaluation for dementia care mapping in Germany used adherence, dosage, participant responsiveness and quality of delivery as evaluation criteria [ 14 ].…”
Section: Introductionmentioning
confidence: 99%